Sr-Nd-Pb isotope systematics of fine sediments from the modern rivers in SW Japan: Implications for sediment provenance of the Northwest Pacific. Issue 3 (1st June 2020) - Saitoh, Yu; Tanimizu, Masaharu; Ishikawa, Tsuyoshi
Graphical abstract: Highlights: The first report of Sr-Nd-Pb isotope ratios of riverine fine sediments in SW Japan. The Sr-Nd-Pb isotope ratios vary widely reflecting the watershed geology. The Kuroshio Current drives the long-distance transport of fine sediments. Abstract: As reference data for comprehensive provenance analyses of deep-sea sediments in the Northwest Pacific region, we present Sr-Nd-Pb isotopic compositions of fine sediments sampled from 48 rivers in southwest Japan. Sr-Nd-Pb isotope ratios are reliable indicators of sediment sources. Although isotopic data of fine sediments in Chinese arid regions, known to be Asian dust sources, are abundant, comparable data from southwest Japan are scarce, even though southwest Japan, owing to its tectonic activity, is a major sediment source to the Northwest Pacific. Sr-Nd-Pb isotope ratios of our riverine fine sediment samples vary greatly ( 87 Sr/ 86 Sr, 0.707–0.724; 143 Nd/ 144 Nd, 0.5120–0.5129; 206 Pb/ 204 Pb, 18.16–18.89; 207 Pb/ 204 Pb, 15.55–15.66; and 206 Pb/ 204 Pb, 38.13–39.09), and these variations are clearly dependent on the principal geology of each river's watershed. These results indicate that these isotope ratios can be effectively used to discriminate the geological sources of the sediments. Sediments from watersheds dominated by Quaternary volcanic rocks have the lowest 87 Sr/ 86 Sr and Pb isotope ratios and the highest 143 Nd/ 144 Nd ratios, whereas sediments from watersheds dominated by accretionary sedimentary rocks generally have high 87 Sr/ 86 Sr and Pb isotope ratios and low 143 Nd/ 144 Nd ratios, but their specific values vary depending on the age and geographic location of the rocks. The isotope compositions of sediments from watersheds with exposed Cretaceous granitic and metamorphic rocks are also distinctive. Comparison between the isotope ratios of Japanese river sediments and the Northwest Pacific seafloor sediments suggests the importance of sediment transport by the Kuroshio Current to the Northwest Pacific.